CD4/CD8 Ratio in Mediastinal Lymph Nodes Involved by Sarcoidosis: Analysis of Flow Cytometry Data Obtained by Endobronchial Ultrasound-guided Transbronchial Needle Aspiration. Issue 4 (October 2016) - Ruiz, Sory J.; Zhang, Yaxia; Mukhopadhyay, Sanjay
Abstract : Background: Despite mixed results in the literature, some clinicians continue to consider an elevated CD4/CD8 ratio in bronchoalveolar lavage (BAL) fluid to be supportive of a diagnosis of sarcoidosis. However, the CD4/CD8 ratio in mediastinal lymph nodes involved by sarcoidosis has not been extensively studied. The primary aim of this study was to evaluate the utility of the CD4/CD8 ratio in mediastinal lymph node aspirates obtained by endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) for diagnosing sarcoidosis. Methods: Our archives were searched for EBUS-TBNAs in which mediastinal lymph node aspirates had been submitted for flow cytometry (n=160). Clinical and pathologic findings in these cases were reviewed retrospectively. Cases were included in the study if they had (1) a clinical diagnosis of sarcoidosis supported by cytopathologic confirmation of non-necrotizing granulomas in EBUS-TBNA–derived lymph node aspirates (23 cases), or (2) a pathologically confirmed non-neoplastic diagnosis other than sarcoidosis (7 cases). Cases that did not fulfil these criteria were excluded (130 cases). Results: The CD4/CD8 ratios in mediastinal lymph nodes and BAL fluid were compared. The CD4/CD8 ratio was elevated in mediastinal lymph nodes in 12/23 (52%) cases of sarcoidosis and 3/7 (43%) pathologically confirmed nonsarcoid cases. BAL fluid had been concurrently submitted for flow cytometry in 20/23 cases of sarcoidosis and 5/7 nonsarcoid cases. CD4/CD8 was elevated in BAL fluid in 9/20 (45%) cases of sarcoidosis and 2/5 (40%) nonsarcoid cases. Conclusion: As in BAL fluid, the CD4/CD8 ratio in mediastinal lymph nodes involved by sarcoid granulomas is highly variable and does not reliably confirm or exclude sarcoidosis.